Potencialidades e caracterização da qualidade das águas subterrâneas salobras para produção biossalina no semiárido cearense - Lessa, Carla Ingryd Nojosa (2023)
Brackish water is an alternative source for arid and semi-arid regions, given the scarcity of low salinity water for use in agriculture and other productive activities. The study was divided into two chapters. The first aimed to evaluate the potential of wells with brackish water for 21 plant production systems and 7 animal production systems, in a representative area of the Brazilian semi-arid region, Ceara. The study was developed using a database of wells in the State of Ceará, provided by the Superintendency of Hydraulic Works - SOHIDRA and by the Mineral Resources Research Company - CPRM. The database includes wells drilled from 1987 to 2021, totaling 25,497 wells, of which 6,284 wells have brackish water (water electrical conductivity from 0.8 dS m-1) and flow from 0.5 m3 h-1. Checking the productive potential of brackish groundwater in the Brazilian semi-arid region does not depend only on the tolerance of the crop and animals to salinity, but on the dataset of the production system (degree of tolerance to salinity and water demand) and the water source (water salinity and flow rate). Plant production systems with lower water requirements (forage palm, supplementary irrigation, hydroponic cultivation and seedling production), even with salt stress tolerance levels, showed better results than more tolerant plant species. Raising poultry, sheep and goats are excellent options for the semi-arid region, using brackish waters. The second chapter aimed to evaluate and classify the quality of these waters for irrigation purposes. The study was carried out in the State of Ceará, using reports composed of the chemical characteristics of water from wells in the hydrographic basins of the Curu and Banabuiú rivers. The Curu waters showed the greatest restriction in terms of electrical conductivity (average of 3.76 dS m-1), in addition to having the highest Sodium Adsorption Ratio (5.96 mmol L-1) and the highest amount of total solids obtained (2,460.1 mg L-1), in comparison with the waters of Banabuiú (EC = 2.72 dS m-1, RAS = 3.87 mmol L-1; STD = 1,763.07 mg L-1). The waters of Banabuiú and Curu are classified for the most part (68,23% and 53,16%, respectively) as waters with moderate salinity problems and low risk of s (less than 10% of the wells present risks of sodicity). Thus, the definition of the potential of groundwater brackish water must consider the restrictions imposed mainly by the salinity of the water. It is concluded that the brackish groundwater in the semi-arid region of Ceará, even with low flows and the presence of salts, can generally guarantee plant production and animal husbandry, allowing the development of thousands of small businesses in the Brazilian semiarid region.